A note on a dynamic network model with homogeneous structure - Long, Yuhang; Huang, Tao (Statistics & probability letters, 2022)
In this note, we establish central limit theorems for the estimators of both heterogeneity and homophily parameters in a dynamic network model with homogeneous structure when the number of nodes and the number of dynamic networks go to infinity.